Maritime remote inspection technology in hull survey & inspection: A synopsis of liability issues from a European Union context. Issue 4 (2nd October 2021) - Alexandropoulou, Vera; Johansson, Tafsir; Kontaxaki, Klimanthia; Pastra, Aspasia; Dalaklis, Dimitrios
ABSTRACT: Vessel hull inspection is a regulatory obligation. Adherence to procedural requirements forged by classification societies helps avoid numerous adverse consequences. In this era of technological innovation, drones, crawlers and underwater submersibles, aptly known as Remote Inspection Technologies, represent emerging technologies, and are being tested to conduct surveys and inspections that will gradually replace human presence on board ships and in-water. However, counter arguments have also emerged against the usage of these AI-based alternatives. Liability is one crucial drawback that could potentially discourage innovation and market growth, especially at the European Union level. Ship owners require a "safety net" as they are a part and parcel of global commerce. Then again, survey and inspection via technologies require the involvement of multiple actors, which makes it difficult to apportion liability. Solutions are required, especially at the European Union level, so that member states could move forward in a spirit of partnership, and nurture and foster technological innovation through partnership. Against the foregoing, this article delves into the European Union liability landscape and outlines some of the critical challenges and strategic ways forward for consideration.